Nivel de conocimiento materno sobre alimentación complementaria y el estado nutricional del niño de 1 años Rio Seco Distrito del Porvenir - Pérez Salinas, Leslie Erika (2011)
This research study on a quantitative, descriptive, correlational, was held at the Health Post "Rio Seco" in the District El Porvenir-2011, in order to determine the relationship between the level of maternal knowledge about food complementary and nutritional status of children of 1 year. The sample universe consisted of 127 mothers with their respective child who met the inclusion criteria in research. For data collection using 2 instruments: Level of Knowledge Survey on Complementary Feeding and Maternal Sheet Assessment of nutritional status of children of 1 year. The information obtained was processed in SPSS 15.0 and analyzed by the test statistic "chi square". The results are presented in tables of single and double entry, after the analysis has led to the following conclusions: The level of maternal knowledge on complementary feeding is regular in a 52.8 per cent, is deficient in a 35.4 percent and is good in a 11.8 percent. The nutritional status of children one year of age according to weight / age: 37 percent are overweight, 51.2 percent are normal, and 11.8 percent are malnourished. According to theheight / age: 56.7 percent are normal, and 43.3 percent have short stature. According to the weight / height: 55.9 percent are normal, 29.1 percent are overweight and 15 percent have severe malnutrition. Highly significant relationship exists between the level of maternal knowledge on complementary feeding and nutritional status of children a year